2019
DOI: 10.1016/j.jas.2019.105035
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Mycobacterium leprae genomes from the mediaeval sites of Chichester and Raunds in England

Abstract: We examined six skeletons from mediaeval contexts from two sites in England for the presence of Mycobacterium leprae DNA, each of the skeletons displaying osteological indicators of leprosy. Polymerase chain reactions directed at the species-specific RLEP multicopy sequence produced positive results with three skeletons, these being among those with the clearest osteological signs of leprosy. Following in-solution hybridization capture, sufficient sequence reads were obtained to cover >70% of the M. leprae gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The technical regime is the same as that used by us in other projects, for example in genotyping of Mycobacterium tuberculosis and Mycobacterium leprae DNA in human bones (e.g. Bouwman et al, 2012;Kerudin et al, 2019), where contamination with PCR amplicons would be evident when next-generation sequencing reads are mapped to the reference sequences. We have never observed such contamination.…”
Section: Authenticity Of the Resultsmentioning
confidence: 99%
“…The technical regime is the same as that used by us in other projects, for example in genotyping of Mycobacterium tuberculosis and Mycobacterium leprae DNA in human bones (e.g. Bouwman et al, 2012;Kerudin et al, 2019), where contamination with PCR amplicons would be evident when next-generation sequencing reads are mapped to the reference sequences. We have never observed such contamination.…”
Section: Authenticity Of the Resultsmentioning
confidence: 99%
“…MTB bacilli travel to bone through the circulatory system and favor areas of hematopoietic marrow in the skeleton such as the vertebral bodies and long bone epiphyses in adults with additional foci in flat bones of the crania and diaphyses of long bones in children (Lewis, 2018;Roberts and Buikstra, 2019). The common diagnostic lesions of skeletal MTB are resorptive foci in the vertebral bodies and joint regions, with the less-specific abnormal bone formation on the pleural surface of ribs providing an additional indicator (Roberts and Buikstra, 2019).The extraction and identification of M. tuberculosis complex DNA in skeletal remains has provided an additional pathway to diagnosis (Harkins et al, 2015;Kerudin et al, 2019;Müller et al, 2014;Sabin et al, 2020;Zink et al, 2003), and has demonstrated that MTB diagnosis based on skeletal lesions alone undercounts the number of people infected in ancient communities.…”
Section: Tuberculosis (Mtb)mentioning
confidence: 99%